(untitled) (Annals of Medical Research, 2021)
Aim: One of the methods used for the diagnosis of childhood respiratory diseases is flexible fiber optic bronchoscopy (FFB). This diagnostic method allows examination of the nose, pharynx, larynx, and tracheobronchial tree. In this study, we present 2 years of FFB experience and highlight its diagnostic advantages in pediatric medicine. Material and Methods: We retrospectively evaluated 213 FFB procedures that were performed between March 2017 and April 2019. Age, sex, FFB indication, bacterial growth in bronchoalveolar lavage (BAL) analysis, the presence of pathological bronchoscopy findings and complications after bronchoscopy were assessed.Results: Of the 213 patients included in the study, 116 (54%) were female and 97 (46%) were male. The mean age was 4.7 ± 6.32 months. The most common indications for bronchoscopy were abnormal radiological findings (30.5%), stridor (13.6%), and chronic cough (11.3%). In 152 patients (71%), diagnostic and therapeutic findings were obtained after bronchoscopy. Transbronchial biopsy was performed in eight patients for whom the etiology could not be determined; a diagnosis was obtained in five of these patients. Bacterial growth in BAL was detected in 68 patients (32%). Temporary complications developed in 17 patients (7.9%) with the most common complication being coughing during the procedure in 8 patients (3.8%).Conclusion: FFB is an important method that allows visualization of the upper and lower airways. The widespread use of pediatric FFB will enable early and non-invasive diagnosis of many respiratory diseases.